Naphthoquinone-derived ZSW-4B induces apoptosis in triple-negative breast cancer via AMPK signalling activation - Xiyuan Hu; Hongdou Liu; Tiao Luo; Ling Chen; Ting Peng; Min Wen; Wensong Luo; Qunfang Xu; Yuanzhu Xie; Mo Li; Mingquan Liu; Xiaohe Liu; et al. (Scientific Reports)
Abstract Triple-negative breast cancer (TNBC) is the most malignant molecular subtype of breast cancer and is characterized by aggressiveness, high mortality, significant heterogeneity, and poor prognosis. AMPK plays a critical role in maintaining the cellular energy balance, and its inactivation is associated with malignant breast cancer. Here, we identified the pharmacological mechanism of the 1,4-naphthoquinone derivative ZSW-4B. MTT, colony formation, and nude mouse xenograft tumour models demonstrated that ZSW-4B selectively inhibits the proliferation of TNBC cells both in vitro and in vivo. Flow cytometry and Western blot analysis revealed that ZSW-4B induces apoptosis in TNBC cells. Phosphoproteomic analysis revealed activation of the AMPK signalling pathway by ZSW-4B. Additionally, the application of the CRISPR-Cas9 system to genetically knockout AMPK in TNBC cell lines was demonstrated to reverse the antitumour effects elicited by ZSW-4B both in vitro and in vivo. In summary, ZSW-4B inhibits TNBC by inducing cellular apoptosis through the activation of AMPK.